PENGEMBANGAN BUKU PENUNTUN PRAKTIKUM IPA BERBASIS INKUIRI TERBIMBING UNTUK SMP KELAS VII SEMESTER II - Handayani, Lena Putri; F, Farida; Anhar, Azwir (Kolaboratif, 2014)
Biology as a part of science has correlate with the laboratory activities, observations, research, experiment and practice. Curriculum 2013 emphasizes constructivist learning with one of the Graduate Competency Standards (SKL) to Junior High School students are able to define problems, propose and test hypotheses, designing and assembling the instrument, process, interpret, and present data systematically. As one of the effort to achieve the SKL is implementing Guided inquiry-based laboratory activities. The purpose of this study was to produce a valid, practical, and effective lab manual based guided inquiry for high school grade 7th in 2nd semester. The type of this research is the development of research. The lab manual based guided inquiry was developed by using a four-D-models. Define phase is to analyze the curriculum for Biology grade 7th at 2nd semester that related to practical activities, the content structure analysis, students analysis and concepts analysis. At the design phase is done the design of lab manual based guided inquiry approach. At develop phase is done by validation the lab manual and did the limited field-testing. Disseminate phase uncommitted coverage. Data collection instrument used in this questionnaire for teachers and students, students motivation questionnaire, observation of students activity sheets and tests students learning outcomes. Tested practical handbook is limited to 30 students of SMP 2 Tanjung Ampalu in grade 7th. The results of this study is the lab manual based guided inquiry for high school grade 7th in 2nd semester. The lab manual is valid, practical, and effective based on validation sheet and field-testing. Â